Prallethrin poisoning: A diagnostic dilemma - Alka Chandra; Madhu B Dixit; Jayant N Banavaliker (Wolters Kluwer Medknow Publications, 2013)
Pyrethroid insecticides are very widely used in agriculture and household due to their high effectiveness and low toxicity in humans. Despite their extensive worldwide use, there are a few reports of human pyrethroid poisoning. The poisoning has a varied presentation and its symptoms overlap with those of other compounds, which can lead to misdiagnosis. We present a case of poisoning with prallethrin, a pyrethroid compound, commonly available as All-Out.